Integrasi Pendidikan Islam dan Sains Perspektif M Amin Abdullah dan Imam Suprayogo - Hamzah Fatih; Siti Choiriyah; Hamdan Maghribi (Jurnal Pendidikan Islam, 2023)
The Integration of Islamic Education and Science Perspectives of M. Amin Abdullah and Imam Suprayogo is an article that discusses the integration between Islamic education and science which is becoming an increasingly important topic in the modern era. This article aims to provide a better understanding of the integration of the two fields, as well as strategies to achieve it. The method used in this research is the literature research method. Data were analysed through three stages, namely data reduction, data presentation, and conclusion drawing. The research results of this article, M. Amin Abdullah and Imam Suprayogo discuss the basic concepts of science and Islam, challenges in integrating science and Islam, and strategies to achieve integration. They argue that science and technology have become an important part of modern human life, and therefore Islamic education should integrate science concepts into its curriculum. Conversely, science should also consider Islamic values in the development of technology and its applications. In addition, the integration of Islam and science pioneered by both is the scientific spider web at UIN Sunan Kalijaga Yogyakarta and the metaphor of the tree of science at UIN Maulana Malik Ibrahim Malang. The closeness of their ontological, epistemological, and axiological frameworks gave birth to the concept of "interconnection integration" at UIN Yogyakarta and "ulul albab" at UIN Malang.